Authentic assessment strategies in virtual and face-to-face higher education contexts. Experience for pre-service teacher education - Fuenzalida Valdebenito, Claudia (2024)
Introduction: Research on learning evaluation in Higher Education has had a significant development seeking to modify its transmissive logic and incorporate current knowledge on training and learning of professional skills. Purpose: Analyze, implement, and suggest authentic assessment strategies at different levels of a pre-service teacher education program for use in face-to-face and virtual contexts. Method: Action research that takes place in a Chilean Jesuit university where authentic evaluation is promoted in its pedagogical model. The study has two stages: Diagnosis - questionnaire (N=102) and discussion group are applied to university students - Application of innovative evaluation strategies developed by university teachers between the first and fourth years of the program. Results: Students and teachers suggest improvements in instructions and correction criteria and in feedback and participation. Based on this, an innovative evaluation strategy is implemented in five key courses of the study plan. Discussion: Five key orientations are described to develop authentic evaluation strategies in university contexts and contribute to compliance with quality standards and criteria in higher education: contextualization; complex skills assessment; anticipate expected performances; promote evaluative judgment in the students themselves and plan forms of feedback.